Thermodynamic performance study on gas-steam cogeneration systems with different configurations based on condensed waste heat utilization. (1st July 2022) - Zhang, Hongsheng; Liu, Xingang; Hao, Ruijun; Liu, Chengjun; Liu, Yifeng; Duan, Chenghong; Qin, Jiyun
Abstract: In view of the limited application of the traditional water-cooled GSPP (gas-steam combined cycle power plant) in water-deficient areas, an air-cooled GSPP is proposed based on AHP (absorption heat pump) to achieve conservation of energy and water in this paper. The thermodynamic performance is comprehensively compared with three other configurations from both the energy and exergy analysis perspectives. Four cogeneration systems are considered: traditional water-cooled GDES (GSPP with direct extraction steam for heating), water-cooled GAS (GSPP with AHP system), air-cooled GDES and air-cooled GAS. Compared with water-cooled GDES, net output power, energy and exergy efficiencies increase by 17, 815 kW, 1.43% and 1.53% in air-cooled GAS with 384, 382 kW heating capacity. The results demonstrate that the performance of an air-cooled GAS can surpass that of a traditional water-cooled GDES, which shows that the energy-saving effect of waste heat recovery can compensate for the performance reduction caused by air cooling modification. Therefore, the traditional water-cooled GDES can be modified into an air-cooled GAS to implement dual purposes of saving energy and water in water-starved regions. The water-cooled GAS achieves the best performance and should be selected in water-rich areas. This research can provide theoretical support for different energy- and water-saving modification needs. Highlights: Proposed diverse combinations of waste heat recovery and cooling modes. Explored the measure to achieve dual purposes of saving energy and water. Established thermodynamic models from perspectives of energy and exergy. Performances changes are revealed from qualitative and quantitative aspects.